β-Glucan and parasites - Vetvicka V.; Fernandez-Botran R. (Helminthologia, 2018)
Immunosuppression caused by parasitic infections represents the foremost way by which the parasites overcome or escape the host’s immune response. Glucan is a well-established natural immunomodulator with the ability to significantly improve immune system, from innate immunity to both branches of specific immunity. Our review is focused on the possible role of glucan’s action in antiparasite therapies and vaccine strategies. We concluded that the established action of glucan opens a new window in treatment and protection against parasitic infections.